2000
DOI: 10.1111/j.0901-9928.2000.870108.x
|View full text |Cite
|
Sign up to set email alerts
|

Supernatants from Macrophages Stimulated with Microcystin‐LR Induce Electrogenic Intestinal Response in Rabbit Ileum

Abstract: Microcystin-LR is a cyclic heptapeptide hepatotoxin produced by the cyanobacterium Microcystis aeruginosa. This microorganism often forms toxic blooms in freshwater lakes and reservoirs for drinking water supply, producing serious disorders in humans and animals. Some have suggested that certain biological activities of microcystin may depend upon the stimulation of immune cells. Therefore, the aims of this research were to examine electrogenic intestinal secretion, in vitro, caused by the supernatants from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
(48 reference statements)
1
14
2
Order By: Relevance
“…Currently, our results illustrate that MC-LR is able to disturb the rabbit immune system and there is time-dose response relationship in the MC-LR-induced perturbation, which clearly indicates the comprehensive effects on Th1, Th2 cells, and probably accessory cells like macrophages and natural killer (NK) cells. Our results are not consistent with previous findings the dynamics of cytokins production (Rocha et al, 2000;Chen et al, 2004), probably due to the different experimental model used. Since our data are unable to furnish us with information on how MC-LR modulates the immune system at the cellular and molecular levels, more studies are required to elucidate the detailed immunotoxic mechanism of MC-LR in vivo.…”
Section: Discussioncontrasting
confidence: 99%
“…Currently, our results illustrate that MC-LR is able to disturb the rabbit immune system and there is time-dose response relationship in the MC-LR-induced perturbation, which clearly indicates the comprehensive effects on Th1, Th2 cells, and probably accessory cells like macrophages and natural killer (NK) cells. Our results are not consistent with previous findings the dynamics of cytokins production (Rocha et al, 2000;Chen et al, 2004), probably due to the different experimental model used. Since our data are unable to furnish us with information on how MC-LR modulates the immune system at the cellular and molecular levels, more studies are required to elucidate the detailed immunotoxic mechanism of MC-LR in vivo.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies demonstrated that MC-LR can stimulate the release of cytokines, particularly IL-1β (Nakano et al 1991;Fujiki and Suganuma 1994;Rocha et al 2000); however, the results of our present experiment were not in agreement with those of previous reports, though the transcription level of IL-1β in the spleen was increased at 7, 14 and 21 d postinjection, it was not significantly different from control groups. In the present study, we observed a strong down-regulation of IL-1β in the spleen at 1 and 2 d postinjection followed by increase in the transcription levels at other time points, which suggests that the decrease in transcription levels of IL-1β, at least partly, ascribed to MC-LR.…”
Section: Ay391782contrasting
confidence: 99%
“…Recently, some cytokines have been studied to explore the immunomodulatory effects of MCs. The variations in the transcription levels of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and inducible nitric oxide synthase (iNOS) genes were analyzed in macrophages stimulated by MCs (Pahan et al 1998;Rocha et al 2000;Chen et al 2004). Although the effects of MCs on mammalian immune system have received increasing attention, those effects of MCs on fish immune system have been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium orthovanadate was dissolved in cell culture medium. The final concentrations of inhibitors were based on comparisons with concentrations reported in literature: cantharidin, 5 M (28), microcystin LR, 5 nM (29,30), and triptolide, 0.5 M (31). Sodium orthovanadate was used at a final concentration of 1 mM (32,33).…”
Section: Cell Isolation and Culturementioning
confidence: 99%